ISLAMIC WORLDVIEW: KONSTRUKTIVISME FILSAFAT DAN TEOLOGI PENDIDIKAN - Tubagus Syihabudin; Ilzamudin Ma’mur; Agus Gunawan (Universitas Islam Lamongan, 2023)
The Islamic view of science forms the basis of thinking to reach the level of confidence in the future development of science. This study discusses a philosophical perspective based on the Islamic worldview as a scholastic theology. Research shows that based on the ontology of Islamic education, there are two types of knowledge: the science of material substance and immaterial substance. Based on the epistemology of Islamic education, there are two types of knowledge, namely Kasby science and Radunni science. Based on the axiomatic theory of Islamic education, science has two functions: useful for humans in real life and the future. The implications of research with educational theological constructivism strengthen the Islamic worldview in the Islamic education system.